2019
DOI: 10.1108/jeee-10-2017-0080
|View full text |Cite
|
Sign up to set email alerts
|

“I’m a stay at home businesswoman”: an insight into informal entrepreneurship in Jordan

Abstract: Purpose Women and disadvantaged minorities within emerging and developing economies often resort to business activity within the informal economy as a way to overcome various barriers and challenges to formal workforce participation. This paper aims to explore the characteristics, motives, barriers and challenges of female engagement in informal business activities in Jordan. Design/methodology/approach The qualitative analysis used in this paper is based upon empirical findings from semi-structured, in-dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 82 publications
0
41
0
Order By: Relevance
“…The training approach in promoting positive attitudes toward entrepreneurship should be made possible for all students in schools starting in middle school. Furthermore, as per Mehtap et al (2019), given that a substantial amount of JEC 14,5 female entrepreneurship is in the informal sector through businesses run through private homes, successful women could be introduced as role models for young women in a special module for female students. Collaboration with other organizations and training institutions would make this goal achievable.…”
Section: Conclusion Limitations and Directions For Future Researchmentioning
confidence: 99%
“…The training approach in promoting positive attitudes toward entrepreneurship should be made possible for all students in schools starting in middle school. Furthermore, as per Mehtap et al (2019), given that a substantial amount of JEC 14,5 female entrepreneurship is in the informal sector through businesses run through private homes, successful women could be introduced as role models for young women in a special module for female students. Collaboration with other organizations and training institutions would make this goal achievable.…”
Section: Conclusion Limitations and Directions For Future Researchmentioning
confidence: 99%
“…As a result, it is essential to identify the most critical factors influencing women to establish their business in Iraq. Some studies showed that family and financial support are crucial for women entrepreneurs to succeed (Al-Kwifi et al, 2020;Brush, 2019;Erogul et al, 2019;Hassan et al, 2020;Mehtap et al, 2019;Musa & Mansori, 2017), while other scholars argued that entrepreneurship training is essential (Bhatti et al, 2021;Dana et al, 2020;Hutasuhut, 2018;Manolova et al, 2014). Accordingly, not much is known whether these factors are indeed having any effect on women's entrepreneurship in conflict countries like Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…Tlaiss (2014) has observed that a lack of family support is a prominent cultural issue that negatively affects female entrepreneurs in the UAE. Mehtap et al (2019) state that female entrepreneurs may need to get permission from the patriarch of the family to start up the business.…”
Section: Resultsmentioning
confidence: 99%
“…These businesses are considered informal and can be managed from home. A study from Jordan by Mehtap et al (2019) contends that the government thus, needs to revise its rules and regulations to facilitate informal business activities. Social media was also seen as playing an important marketing role for female entrepreneurs (Al Mazrouei and Krotov, 2016; Alakaleek and Cooper, 2018).…”
Section: Resultsmentioning
confidence: 99%